Influenza vaccine coverage among children under the age of 5 years in Poland during 2004-2008 - Nitsch-Osuch, A (Eur J Med Res, 2010)
INTRODUCTION: Influenza is a considerable health problem all over the world. The most important group for influenza vaccination are children: the highest attack rate during community out-breaks of influenza can be found among school-aged children or their family members; children bear a considerable risk for complications due to influenza, leading to an increased need for healthcare resources (including hospitalization). The high level of vaccine coverage among school children could provide protection against influenza among households and could reduce mortality rates among older individuals. OBJECTIVE: The aim of this study was to estimate the influenza vaccine coverage among children younger than 5 years and to find any trends in influenza vaccine coverage in 2004-2008 in Poland. MATERIAL AND METHODS: Official data (number of administrated vaccines and the age of vaccinated individuals) collected by the National Institute of Hygiene, the National Institute of Public Health, and the Central Statistical Office in Poland were analyzed. This data are reported by physicians and collected from reports prepared annually by the Sanitary-Epidemiological Stations at a local level. The vaccine coverage rate was calculated as a percentage of vaccinated individuals among all children under the age of 5 years. RESULTS: The influenza vaccine coverage among children younger than 5 years varied from 1% (2007 and 2008) to 1.9% (2005). The proportion of vaccinated children aged less than 5 compared with the total number of flu shots administrated irrespective of age also varied from 1.4% (2007) to 2% (2005). CONCLUSIONS: The influenza vaccination coverage among Polish children aged less than 5 years is low and has persisted at the same level. More educational activities directed both to patients (parents) and healthcare workers would be needed to improve a general knowledge about influenza vaccination benefits among young children.